Rhetorics for Community Action : Public Writing and Writing Publics. - Ryder, Phyllis Mentzell (Cultural studies/pedagogy/activism., 2012)
Offering both theoretical analysis and classroom advice, Rhetorics for Community Action: Public Writing and Writing Publics, by Phyllis Mentzell Ryder, is a guide to studying and teaching public writing. The book shows how public groups embed competing democratic ideals into the rhetorical structures of their texts, how they work with and against traditional media to spread those ideals, and how teachers can partner with community organizations and support students as they practice public writing in all its complexity.